2020
DOI: 10.1186/s12909-020-02011-w
|View full text |Cite
|
Sign up to set email alerts
|

Lebanese students’ motivation in medical school: does it change throughout the years? A cross-sectional study

Abstract: Background: Students entering medical school are driven by different types of motivation: autonomous motivation, controlled motivation, or amotivation. Motivation types can influence students' performance, outcome and well-being. To our knowledge, this topic has never been studied in Lebanese medical students. This study aims to identify students' motivation types in the first 5 years of medical school at two Lebanese universities (USJ and USEK). It also aims to determine the predominant motivation type of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
3
20
0
2
Order By: Relevance
“…To note that these 15 questionnaires related data was not entered in the final database. The methodology used in similar to the one used in a previous paper [36] Questionnaire and variables…”
Section: Methodsmentioning
confidence: 99%
“…To note that these 15 questionnaires related data was not entered in the final database. The methodology used in similar to the one used in a previous paper [36] Questionnaire and variables…”
Section: Methodsmentioning
confidence: 99%
“…Other studies also pointed out inconsistencies in the number of factors, with extraction of five factors, in which the three types of intrinsic motivation were grouped into a single factor ( 20 , 40 ) , and extraction of three factors ( 41 ) . In a study with Lebanese medical students, PCA was used and the results showed the items converged into a 3-factor solution with explanation of 81.51% of total variance ( 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…When assessing the reliability of the scale factors used in this study, previous studies used the Cronbach’s alpha index, considering the following satisfactory values: 0.48 to 0.98 ( 11 ) , 0.62 to 0.82 ( 7 ) , 0.65 to 0.83 ( 10 ) , 0.68 to 0.83 ( 21 ) , 0.70 to 0.86 ( 16 , 18 ) , 0.74 to 0.92 ( 17 ) , 0.77 to 0.90 ( 19 ) , 0.79 to 0.86 ( 38 ) . The reliability of the factors by Cronbach’s alpha and the composite reliability were considered satisfactory in our study, according to the parameters reported in the literature ( 32 - 33 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed the questionnaire based partly on existing questionnaires [13][14][15]. According to the pretesting feedback from 250 students, the questionnaire was further revised and improved to form the optimised nal version.…”
Section: Questionnairementioning
confidence: 99%